Home medication management problems and associated factors among psychiatric patients using home care pharmacy services at government hospitals in western Malaysia - Christine Li Ling Lau; Cheah Yen Hor; Siew Ting Ong; Muhammad Fadhlullah Roslan; Xin Yi Beh; Dashnilatha Permal; Shamini Rama (BMC, 2022)
Abstract Background Proper home medication management plays a role in improving medication adherence, preserving drug efficacy and ensuring safe medication practices, which is crucial to establish positive treatment outcomes. However, no published studies are available on home medication management among psychiatric patients. The study aimed to identify home medication management problems among psychiatric patients in Malaysia and to examine the associations of inappropriate medication storage and lack of a medication administration schedule with sociodemographic factors, disease insight, number of medications and type of home care pharmacy services (HCPS). Methods This multicentre cross-sectional study was conducted among psychiatric patients using HCPS in six government hospitals in western Malaysia. Data were extracted from the HCPS form used for each visit as per the protocol published by the Pharmaceutical Services Division, Ministry of Health Malaysia. A minimum sample size of 169 was needed. Proportional random sampling was applied. The associations of inappropriate medication storage and lack of medication administration schedule with study parameters were analysed using multiple logistic regressions. Results A total of 205 home visits were conducted with 229 home medication management problems identified; inappropriate medication storage and lack of medication administration schedule topped the list. Inappropriate medication storage was significantly associated with low income [AOR = 4.34 (95% CI 1.17:15.98), p = 0.027], alcohol consumption [AOR = 14.26 (95% CI 1.82:111.38), p = 0.011], poor insight [AOR = 2.34 (95% CI 1.08:5.06), p = 0.030] and part-time HCPS [AOR = 2.60 (95% CI 1.20:5.67), p = 0.016]. Lack of administration schedule was significantly associated with low income [AOR = 6.90 (95% CI 1.46:32.48), p = 0.014], smoking [AOR = 2.43 (95% CI 1.20:4.92), p = 0.013], poor insight [AOR = 5.32 (95% CI 2.45:11.56), p < 0.05] and part-time HCPS [AOR = 2.96 (95% CI 1.42:6.15), p = 0.004]. Conclusions Inappropriate medication storage and a lack of a medication administration schedule are common among psychiatric patients. The study also highlighted the potential of HCPS to improve disease insight and home medication management among psychiatric patients if the service is utilized fully.